2016
DOI: 10.1007/s10266-016-0238-5
|View full text |Cite
|
Sign up to set email alerts
|

Screening tests for predicting the prognosis of oral intake in elderly patients with acute pneumonia

Abstract: Many elderly patients with pneumonia have aspiration pneumonia. Therefore they must temporarily abstain from oral intake. However, it is difficult to predict whether or not they will be able to start oral intake. The reason is the standard method to evaluate deglutition about pneumonia patients has not been established. In this study we aimed to develop a simple and convenient method that predicts the prognosis of oral intake as nutrition among elderly patients with acute stage pneumonia. Participants were 77 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 35 publications
0
17
0
1
Order By: Relevance
“…15 Among swallowing screening tests for patients with acute pneumonia, the RSST (once or more every 30 s) has been reported to be the most useful test for determining whether to restart food intake. 15 The CPF sensitivity, specificity, and area under the curve for evaluating the risk of aspiration when restarting food intake were similar to the RSST values, and there was no significant difference especially for the area under the curve (P ϭ .42), which suggests that the precision of CPF is not inferior to that of the RSST, which is a conventional swallowing screening test. The sensitivity, specificity, and area under the curve might have been similar between CPF and the RSST because the glottic closure is involved in both CPF and the RSST.…”
Section: Cutoff Values and Sensitivity/specificity Of Rsst Results Anmentioning
confidence: 99%
See 2 more Smart Citations
“…15 Among swallowing screening tests for patients with acute pneumonia, the RSST (once or more every 30 s) has been reported to be the most useful test for determining whether to restart food intake. 15 The CPF sensitivity, specificity, and area under the curve for evaluating the risk of aspiration when restarting food intake were similar to the RSST values, and there was no significant difference especially for the area under the curve (P ϭ .42), which suggests that the precision of CPF is not inferior to that of the RSST, which is a conventional swallowing screening test. The sensitivity, specificity, and area under the curve might have been similar between CPF and the RSST because the glottic closure is involved in both CPF and the RSST.…”
Section: Cutoff Values and Sensitivity/specificity Of Rsst Results Anmentioning
confidence: 99%
“…26 The cutoff value of each test was considered as the value of the point closest to the upperleft corner along the ROC. 15 For data analysis, calculations were performed with descriptive statistics (mean Ϯ SD). All analyses were performed using SPSS 24.0 (IBM Corp, Armonk, New York) and the statistical package R 3.1.0 (R Project for Statistical Computing, Vienna, Austria).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, eating and swallowing function were assessed by 81.2% of all respondents, and by virtually all (96.6%) of respondents providing dysphagia rehabilitation. Multiple-choice responses on the content of assessment among respondents practicing assessment revealed that a medical interview was performed by 96.4% of respondents and that a screening test including a repetitive saliva swallowing test (4,5), modified water swallowing test (6)(7)(8), and food test (6) was performed by 93.8% of respondents (Fig. 3B).…”
Section: Content Of Ddcmentioning
confidence: 99%
“…The RSST is used for screening dysphagia, and one of the methods for assessment of swallowing function, as well as the tongue pressure [15]. The RSST is a predictor of aspiration [23,24]. The decrease in tongue pressure may also be a predictor of aspiration in patients after esophagectomy.…”
Section: Discussionmentioning
confidence: 99%